محاولات المدرس لتعزيز دوافع الطالبات في مهارة الكلام بالمدرسة الفتيان التعليمي أتشية (لســـانـنــا (LISANUNA): Jurnal Ilmu Bahasa Arab dan Pembelajarannya, 2021)
This research aims to see and find out the efforts that made by the teacher of Al-Fityan School Aceh to motivate students in speaking skill. The research method used is descriptive qualitative method. The researcher used the theory of Miles and Huberman as the way of data collection and analysis techniques. There are four stages of the techniques, they are: data collection, data reduction, data presentation(data display) andconclusion drawing/verification. The results of this research is the researcher found that the teacher tried to motivate the students in several ways, including: (1) The method that used by the teacher of Al-Fityan School Aceh is a direct method (thariqah mubasyarah) where the method is using Arabic language directly in daily activity without using mother tounge. 2) The use of learning method such as mumarasah takallum al-lughah arabiyyah and expression of language habituation program. (3) The use of media such as picture (shurah), poster (lauhah), and video..
Keywords: teacher effort; motivation; speaking skill